Genetic identity, human blood indices, and sporozoite rates of malaria vectors in Gaa-Bolorunduro, Kwara State, Nigeria - Abiodun Obembe; Adedayo Olatunbosun Oduola; Tolulope Amos Oyeniyi; Abiodun Kanmi Olakiigbe; Samson Taiwo Awolola (Journal of Infection in Developing Countries)
Introduction: To identify the specific Anopheles mosquito sibling species responsible for malaria transmission, determine their vectorial potential, and predict suitable control measures, this study investigated genetic identities, human blood feeding, and sporozoite infection rates of endophilic Anopheles mosquitoes in Gaa-Bolorunduro, a cattle rearing community in Kwara State, Nigeria.